A New Preoperative Planning Technique Can Reduce Radiation Exposure During the Performance of Medial Opening-Wedge High Tibial Osteotomy. Issue 3 (October 2018) - Spitzer, Elad; Ruzbarsky, Joseph J.; Doyle, John B.; Yin, Kaitlyn L.; Marx, Robert G.
Background: Medial opening-wedge high tibial osteotomy (HTO) is one of the most common and effective HTO techniques, in which the proximal tibia is cut medially, leaving an intact lateral hinge of bone that can be opened to a variable amount for the desired correction, but the technical complications of lateral cortex fracture and intra-articular fracture are well described. The lateral bone hinge for medial opening-wedge HTO is crucial. If the hinge is too small, the tibia can fracture and become unstable, requiring further fixation. If the hinge is too large, the osteotomy can propagate into the joint as an intra-articular fracture when opening the osteotomy. Purpose: We propose a new technique that utilizes digital preoperative templating to improve the accuracy of the cut. Preoperative digital templating may allow the surgeon to reproducibly obtain a lateral bone hinge of 10 mm, while also reducing radiation exposure relative to the traditional fluoroscopically assisted technique. Methods: Ten cadaver extremities from five cadavers were matched into pairs and randomized into two groups: those with and without preoperative templating. The templating protocol measures the distance between two points on the medial and lateral cortices, and 20 mm is subtracted to determine the depth of the saw cut (10 mm for the hinge and another 10 mm because the proximal tibia is oval in shape). The control method was done by making the cut using fluoroscopy with tactile feedback. Postoperative computed tomography scans were obtained of all legs to measure the width of the lateral bone hinge. Intraoperative fluoroscopy used during both techniques and the numbers of fluoroscopy shots were recorded. Results: We found neither the treatment group with preoperative planning nor the control group with the conventional technique had bone hinge widths that were different from the ideal 10 mm. The average hinge widths for the treatment and control groups were 11.2 and 11.5 mm, respectively. However, the treatment group was exposed to significantly less intraoperative fluoroscopy during the osteotomy cut. The average total number of fluoroscopy shots was 2.2 in the treatment group versus 6.3 for the control group. Conclusions: This new preoperative planning technique achieves similar accuracy of the lateral bone hinge when compared to current methods but exposes the patient, surgeon, and staff to significantly less intraoperative radiation.